Mental health of children with vision impairment at 11 years of age. (7th March 2016) - Harris, John; Lord, Chris
Abstract : Aim: The purpose of the study was to compare the risk of psychiatric disturbance among sighted and vision‐impaired children aged 11 years. Method: Scores from the parent and teacher versions of the Strengths and Difficulties Questionnaire (SDQ) were used to compare sighted children with: vision‐impaired children; vision‐impaired children with no other reported disabilities or special educational needs; and children with vision impairment and additional disabilities or special educational needs. Logistic regression was used to measure the associations between the independent variables and SDQ scores, and to test for significance of the observed differences. Results: Both parents and teachers scored vision‐impaired children significantly higher on the SDQ compared with sighted children ( p ≤0.000) and a significantly higher proportion of the vision‐impaired children had SDQ scores in the abnormal range ( p ≤0.000). Children with vision impairment and other disabilities or special educational needs were rated as being at greatest risk of psychiatric disorder by both parents (30%) and teachers (22%). Interpretation: Vision impairment among children as young as 11 years of age is associated with an increased risk of psychiatric disorder. What this paper adds: Vision‐impaired children aged 11 years are at risk of psychiatric disorder. Vision‐impaired children with additional special educational needs and disabilities are at greatest risk. Health services should consider how to identify and treat vision‐impaired children at risk of psychiatric disorder. This article is commented on by Hatton on pages660–661 of this issue.